Benchmark definition, 4th edition (BMD4): Foreign direct investment: income, main aggregates (Edition 2019) (OECD International Direct Investment Statistics, 2019)
This dataset on foreign direct investment (FDI) provides a summary of main aggregates in cross-country comparisons of income on equity and interests on income from debt (inward, outward). Data are provided in US dollars, reported currency and as a share of GDP; and are available from 2005 onwards. FDI income data are closely linked to the stocks of investments and are used for analysis of the productivity of the investment and calculation of the rate of return on the total funds invested